2006
DOI: 10.1007/s11099-006-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acacia plantations on net photosynthesis, tree species composition, soil enzyme activities, and microclimate on Mt. Makiling

Abstract: To determine the effectiveness of rehabilitation on improving ecosystem functions, we examined net photosynthetic rate (P N ), tree species composition, soil enzyme activities, and the microclimate (air and soil temperature, relative humidity) of an area on Mt. Makiling that has been rehabilitated and protected from fire for over 12 years. After it was last burned extensively in 1991, restoration was initiated by planting Acacia mangium and Acacia auriculiformis. We selected three areas to study in 2003. Two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…, 2003). N 2 ‐fixing associations occur in most Australian acacias (Lawrie, 1981; Lee et al. , 2006), which usually nodulate with common, but slow‐growing Bradyrhizobium species (Lafay & Burdon, 2001; Rodríguez‐Echeverría et al.…”
Section: Resource Acquisition and Use By Invasive Australian Acaciasmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2003). N 2 ‐fixing associations occur in most Australian acacias (Lawrie, 1981; Lee et al. , 2006), which usually nodulate with common, but slow‐growing Bradyrhizobium species (Lafay & Burdon, 2001; Rodríguez‐Echeverría et al.…”
Section: Resource Acquisition and Use By Invasive Australian Acaciasmentioning
confidence: 99%
“…Australian acacias are well known for their N 2 -fixation abilities (Levine et al, 2003). N 2 -fixing associations occur in most Australian acacias (Lawrie, 1981;Lee et al, 2006), which usually nodulate with common, but slow-growing Bradyrhizobium species (Lafay & Burdon, 2001;Rodríguez-Echeverría et al, 2011). Associations with other nodulating species have also been reported, including Rhizobium, Ensifer, Mesorhizobium, Burkholderia, Phyllobacterium and Devosia species (Marsudi et al, 1999;Lafay & Burdon, 2001;Hoque et al, 2011).…”
Section: Nutrient Acquisitionmentioning
confidence: 99%
“…Therefore, large production of A. mangium is likely supported by high photosynthetic rate from leaves containing high N and efficient P use under enough light, water and limited P conditions. The efficient P retranslocation by A. mangium appears to be a discrepancy with an enhanced P acquisition ability by the significant phosphatase activities (Kojima 2004;Lee et al 2006), because efficient P retranslocation did not occur under sufficient P conditions (Martínez-Sánchez 2005; Richardson et al 2008). These two P use strategies might be caused by differences in P demand by the host plant and its symbiotic microbes.…”
Section: N and P Dynamics In A Mangium And Nutrient Demandsmentioning
confidence: 99%
“…Leguminous Acacia mangium growing in solution cultures or pots were found to efficiently utilise P under P-deficient conditions (Vadez et al 1995;Ribet and Drevon 1996;Nguyen et al 2006). Recent studies showed that tropical legumes had enhanced P acquisition abilities compared to other species (Khanna 1998;Kojima 2004;Lee et al 2006;Houlton et al 2008). A literature survey indicated that extracellular phosphatase activities were significantly higher in soils under N 2 -fixing plants compared to those under non-N 2 -fixing plants (Houlton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some tropical N 2 -fixing trees exhibit specific P acquisition abilities by producing larger extracellular phosphatase [15]. This phosphatase production was larger in soils under A. mangium than those under secondary forests [16]. Houlton et al [17] suggested that N 2 -fixing plants could thrive under P-deficit conditions, such as those encountered in the wet tropics, in part by enhanced phosphatase production using the abundant N resources.…”
Section: Introductionmentioning
confidence: 99%